The Actual Epidemiological Effectiveness of Assessing and Improving the System for Ensuring the Epidemiological Safety of Medical Care for Catheterized Patients - D. V. Kvashnina; O. V. Kovalishena; O. M. Sutyrina; I. V. Ivanov; E. L. Nikonov (Неотложная медицинская помощь)
The basis of optimized conventional system of surveillance and control for catheter-related bloodstream infections (CRBI) was priority in detection and risk assessment an infectious complication of puncture catheterization that substantially justified with inclusion of two main components as an addition to the existing system: monitoring of puncture catheterization, which allows to obtain and analyze data on risk factors for infections associated with the catheterization procedure and subsequent manipulations of the device, standardize approaches to working with a venous catheter and improve the diagnosis of CRBI; assessment of ensuring the epidemiological safety of medical care for catheterized patients. Epidemiological efficiency risk-based surveillance, primarily determined to reduce the incidence of CRBI by 1.8 times compared to initially defined real incidence: 12.5‰ (95% CI — CI 11,8–13 2) vs 22.8‰ (95% CI 21,1–24,5) catheterized patients, p=0.0001.